تصميم وتنفيذ نظام شحن بطاريات شمسي متطور - محمود علي; شيحا بلال; العلي سحر (Latakia University Journal -Engineering Sciences Series, 2017)
إن الهدف الرئيس لهذا البحث هو تصميم نظام شحن بطاريات بالطاقة الشمسية الأعظمية, وقد تم استخدام نظام تتبع للاستطاعة الأعظمية Maximum power point tracking (MPPT) system, مكون من مبدل (رافع – خافض) للجهد المستمر buck-boost Direct Current DC/DC converter, المبدل مقاد بواسطة متحكم صغري, تمت برمجته بطريقة الموصلية المتزايدة Incremental Conductance (InCond) وتعد طريقة سهلة وموثوقة للتتبع. تم اختبار نظام الشحن المقترح والنتائج التي حصلنا عليها تؤكد التحكم الدائم بعملية الشحن للبطارية. تم إجراء دراسة مقارنة مع جهاز شحن شمسي يعتمد التحكم بعرض النبضة PWM, وقد أوضحت النتائج أنه تم شحن المدخرة الموصولة مع نظام الشحن المقترح بوقت أسرع, مع الأخذ بالحسبان ساعات الإشعاع الشمسي باليوم, ومواصفات اللوح الشمسي المستخدم, وهذا يؤكد وثوقية أداء نظام الشحن المقترح. The main goal of this search is to design maximum solar power batteries charging system, Maximum power point tracking (MPPT) system is used in the photovoltaic (PV) system consisting of a buck-boost Direct Current DC/DC converter, which is controlled by a microcontroller unit, The microcontroller is programmed with a simple and reliable MPPT called Incremental Conductance (InCond). The designed battery charger was tested, and the results obtained had insured about the permanent control on the battery charging. Comparison study was done, with PWM solar charger controller, it was obvious by The experimental results, that the battery get charged in a very short time period considering of the solar sun light hours per day, and the characteristics of the used solar panel, which confirm the reliable performance of the suggested charging system.